Hubungan Pola Konsumsi Zat Besi dan Pengetahuan Tentang Anemia Dengan Kejadian Anemia Remaja Putri di SMA Negeri 1 Seputih Agung Lampung Tengah - Puspasari, Nova Tri; Nurhartanto, Adhi; Nurdiansyah, Tubagus Erwin (CV. Rayyan Dwi Bharata, 2025)
Anemia is a condition where the hemoglobin (Hb) level in the blood is less than normal where the normal limit is 12 g/dl. Poor consumption patterns and lack of knowledge about anemia can cause anemia. This study aims to determine the relationship between iron consumption patterns and knowledge about anemia with the occurrence of anemia in adolescent girls at SMA Negeri 1 Seputih Agung. This study used a Cross Sectional design conducted at SMA Negeri 1 Seputih Agung from June 2024. The study population was all female adolescents in class XI at SMA Negeri 1 Seputih Agung, totaling 107 people. The incidence of anemia was obtained by measuring hemoglobin, and data on iron consumption patterns with SQ-FFQ, and data on knowledge about anemia using a questionnaire. The study used the Chi-Square method. The results showed 44.0% of female students experienced anemia. Adolescent girls have poor iron consumption patterns (91.7%) and half of adolescent girls have poor anemia knowledge (90.5%). There is a significant relationship between iron consumption patterns and the incidence of anemia in adolescent girls (p = 0.014), and there is no significant relationship between knowledge about anemia and the incidence of anemia in adolescent girls (p = 0.078). With the relationship between iron consumption patterns and knowledge about anemia with the incidence of anemia, there should be counseling in schools about iron consumption patterns and knowledge about anemia in order to reduce the incidence of anemia.